Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2147/idr.s386497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant TB Among Smear-Positive Pulmonary TB Patients in Banadir, Somalia: A Multicenter Study

Abstract: Background Tuberculosis (TB) is an infectious disease that is the second most common cause of death from a single infectious agent. TB infection affects anyone, regardless of age, gender, and ethnicity. Drug-resistant TB is a serious public health problem, which needs treatment with a second-line anti-TB drug and it includes poly-drug resistance (PDR), multi-drug resistance (MDR), and extensive drug resistance (XDR). The goal of this research is to find out the prevalence of MDR TB among pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…One possible reason for the relatively low treatment success rate is the high prevalence of drug-resistant TB strains in Benadir, Somalia. 4 Drug resistance is a major challenge in TB treatment, as it requires more complex and challenging treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for the relatively low treatment success rate is the high prevalence of drug-resistant TB strains in Benadir, Somalia. 4 Drug resistance is a major challenge in TB treatment, as it requires more complex and challenging treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…1 Adult males account for 56% of all cases of TB, whereas adult females account for 33% and children for 11%. 3 , 4 The World Health Organization (WHO) estimates that Mycobacterium tuberculosis (MTB), the TB causative organism, infects one-third of the world’s population, or roughly two billion individuals. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Considering the ratio of infections among males vs females, one study reported that the split between males and females with multi-drug resistant tuberculosis was 70.4% and 29.6% respectively [ 201 ], In a study conducted in patients with resistant tuberculosis in Ghana, the ratio of males and females was 69.6% and 30.4% respectively [ 202 ], whilst in another study conducted in Egypt, the ratio of males and females was reported as 67.5% and 32.5%, respectively [ 203 ]. Moreover, in a similar research work conducted in Ethiopia 65.3% male and 34.7% female has multi drug resistant TB [ 204 ].…”
Section: Discussionmentioning
confidence: 99%